Associations of Socioeconomic Status and Physical Activity With Obesity Measures in Rural Chinese Adults - Pan, Mingming; Tu, Runqi; Gu, Jianjun; Li, Ruiying; Liu, Xiaotian; Chen, Ruoling; Yu, Songcheng; Wang, Xian; Mao, Zhenxing; Huo, Wenqian; Hou, Jian; Wang, Chongjian (Frontiers in Public Health, 2021)
Background: Although independent associations of socioeconomic status (SES) or physical activity (PA) with obesity has been well documented in urban settings, their independent and joint associations on obesity measures are limited in rural regions. Methods: Almost thirty-eight thousand (n=37,922) individuals were included from the Henan Rural Cohort Study. The International Physical Activity Questionnaire (IPAQ) was used to evaluate PA. Obesity was reflected by body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), body fat percentage (BFP), and visceral fat index (VFI). The independent and interactive effects of SES and PA on obesity were analyzed by logistic regression models and generalized linear regression models, respectively. Results: Compared with high education level, the OR (95%CI) of obesity defined by BMI with low education level was 1.466 (1.337, 1.608), 1.064 (0.924, 1.225), and 1.853 (1.625, 2.114) in total population, men and women, respectively. Besides, the OR (95%CI) of obesity defined by BMI associated with per capita monthly income were 1.089 (1.015, 1.170), 1.192 (1.055, 1.347), 1.038 (0.951, 1.133) in total population, men and women, respectively. Similar results had been observed in other obesity measures. Negative interactive association of low education level and PA on obesity measures were observed only in women (all P＜0.05). Conclusions: This study suggests that women are more susceptible to obesity concerning low SES and that adequate PA may be a potential target for mitigating the negative effect of low SES on obesity in women. Clinical Trial Registration: The Henan Rural Cohort Study has been registered at Chinese Clinical Trial Register (Registration number: ChiCTR-OOC-15006699). http://www.chictr.org.cn/showproj.aspx?proj=11375.